Michael Faraday e sua bem sucedida forma de comunicação da filosofia natural no século XIX - Leite, Rodrigo Pietro (2017)
Michael Faraday developed forms of communication throughout his life that was later repurposed as a means of spreading and popularizing the science of the time. This thesis presents, as its main focus his work with the Royal Institution and discusses the relationship between his laboratory work and his conferences. In the first case, in order to publicize his work, Faraday used a more complex form of communication addressed to subject scholars and intellectuals, whereas in his lectures aimed at students, laypeople and curious his language was more accessible. The Christmas Conferences, inaugurated in 1825 - with the first participation of Michael Faraday in 1827 - were lectures aimed at raising funds and reaching a young audience, because these minds are more open to new knowledge and, perhaps, willing to apply it in the near future; England was, undergoing industrial expansion, and had a growing need for human material with the capacity to apply specific knowledge and to capture resources. Being an expanding market, England as this time, naturally offered an excellent opportunity for young people. Michael Faraday himself had been encouraged to become a natural philosopher, through such conferences, which he attended as a young man. Several experimental tests performed by Michael Faraday would help formulate fundamental concepts for the understanding of matter. In this study, we focused, in particular, on the experiments developed in order to be used as a means of scientific dissemination, as well as their form of communications, both for an audience familiar with the subject and for the unfamiliar public